Assessment of land degradation in Inner Mongolia between 2000 and 2020 based on remote sensing data - Zhao, Linlin; Jia, Kun; Liu, Xin; Li, Jie; Xia, Mu (Geography and sustainability, 2023)
•Inner Mongolia is a significant ecological security barrier in northern China.•Land degradation status in Inner Mongolia was assessed from the SDG perspective.•The calculation of SDG 15.3.1 takes into account the ecological programs.•Land degradation is curbed with ecological programs implementation in Inner Mongolia. Achieving land degradation neutrality (LDN) worldwide is a significant target of the Sustainable Development Goal (SDG15.3). Inner Mongolia, as a typical dryland region in northern China, has carried out several large-scale ecological restoration programs to combat land degradation. However, there is a lack of comprehensive assessment of its land degradation situation after ecological programs implementation, which is of great significance to supporting SDG15.3 in China. This study analyzed the land degradation situation using the improved SDG15.3.1 calculation framework based on fine resolution data in Inner Mongolia from 2000 to 2020, and finally comprehensively evaluated the land status of the whole region and those subject to ecological programs. The results show that net land restoration proportion of various ecological project regions and whole region continues to increase. The scope of the Grain for Green Program (GGP) had the largest proportion of net land restoration while the Natural Reserve Program (NRP) had the lowest proportion from 2000 to 2020. The net land restoration area of Inner Mongolia during 2000–2010 and 2010–2020 was 35,800 km² and 65,300 km², respectively. Overall, Inner Mongolia has achieved statistically zero growth in land degradation under the governance of ecological restoration programs. Therefore, reasonable planning, well monitoring, and timely assessment of ecological restoration programs are crucial to support SDG15.3. [Display omitted]